An Overview of Anti-trespasser - Jayendra S. Jadhav (Technological Innovation in Engineering Research Vol. 7, 2022)
Security systems nowadays still have limited authentication capabilities and are generic. Such security measures are valid for their intended use. It might be conceivable to overcome obstacles given the advancement of technology and the rise of malicious individuals. The security of one’s important data is the first priority. This project suggests a security technique to raise everyone’s level of security. The application makes an effort to use a user’s presence as a key to open a virtual space. The system needs a mobile device with Bluetooth capabilities, along with the main device you need to secure. The Project’s goal is to closely tie the operating system’s security mechanism so that it can take the necessary precautions to protect data privacy.